The whispers of war [large type] - Kelly, Julia, 1986- (Thorndike Press, a part of Gale, a Cengage Company, 2020)
"August, 1939, Britain watches the headlines in fear of another devastating war with Germany and three childhood friends must choose between friendship or country. Socialite Nora is determined to find her place in the Home Office's Air Raid Precautions Department, while matchmaker, Hazel, tries to mask two closely guarded secrets with irrepressible optimism, and German ex-pat Marie worries that she and her family might face imprisonment in an internment camp if war is declared. When Germany invades Poland and tensions on the home front rise, Marie is labelled an enemy alien, and the three friends find themselves fighting together to keep her free at any cost. The Whispers of War is a moving and unforgettable tale of the power and strength of friendship in a time of conflict."--Publisher description.